Digital literacy and digital teaching competence at the secondary level, province of Huaura, Perú - Méndez-Toledo, Heimer Ali (2021)
The purpose of the study was to determine the relationship between digital literacy and digital teaching competence at the secondary level, UGEL Nº 09 Huaura. The study was of correlational scope, non-experimental cross-sectional design; The sample was made up of 198 high school teachers from urban areas who have permanent access to various technological resources (ICT). Two Likert scale questionnaires were used, which have the corresponding technical procedures that determine their validity and reliability. The results indicate that there is sufficient statistical evidence to determine the existence of a relationship between digital literacy and digital teaching competence (? = 0.707 and p value = 0.000); consequently, an adequate level of digital literacy contributes to a better performance of digital skills in teachers; A significant linear relationship was also found between digital literacy and each of the dimensions of digital teaching competence at the secondary level, jurisdiction of the UGEL N° 09 of the province of Huaura.